How has the strict lockdown during the SARS-COV-2 outbreak changed the diet of Spaniards? - Toni Mora; Eleonora Fichera; Beatriz G. Lopez-Valcarcel (Elsevier, 2023)
Purpose: We investigate the impact of a specific macroeconomic shock that occurred as a response to the SARS-COV-2 outbreak, namely the strict lockdown imposed in Spain on the March 14, 2020. Methods: We use fortnightly purchase data relating to over 50,000 households from a supermarket chain in Catalonia from March to June in 2019 and 2020. Using a panel data approach, we analyse the impact of the lockdown on the caloric content, sugar composition, and alcohol content in beverages and food purchases bought before and after lockdown. We corrected our results to take into account the likelihood of stockpiling. Results: The lockdown is related to an increase in unhealthy beverage and food purchases. We find heterogeneous effects across groups of the sample based on cardholder characteristics. Families with children or babies and those in the upper two income quintiles had the unhealthiest changes. As the lockdown went through phases of relaxation, households made better food decisions but maintained unhealthy beverage choices. Conclusions: The very restrictive lockdown negatively impacted the characteristics of food and beverage purchases made by Spaniards. However, we are unsure whether there was substitution to restaurant and bar visits. Additional work to find out whether there were permanent changes in purchasing behaviour after lockdown ended is needed in the future.